Reconciling the views of ‘Umar b. ‘Abd al-‘Aziz (d. 101 AH/720 CE) on mosque decoration - Omer, Spahic (Hamdard Foundation Pakistan, 2019)
This paper discusses the views of the 8th Umayyad Caliph, ‘Umar b. ‘Abd al-‘Aziz (‘Umar II), on mosque decoration. It resolves an ostensible inconsistency between what he as the governor did to the Prophet’s Mosque in Madinah, and what he intended to do to the great Umayyad Mosque in Damascus after becoming the Caliph. The paper concludes that there was no inconsistency whatsoever in ‘Umar II’s actions. This becomes evident when the matter is thoroughly explored against the backdrop of the extraordinary personality of ‘Umar II, as well as the prevailing socio-political, cultural and religious developments in the Muslim Umayyad society. ‘Umar II only acted along the lines of the general laws that governed the birth and evolution of the identity of Muslim architecture, at the center of which stood mosque decoration. Thus, after presenting at the beginning of the paper ‘Umar II’s views in question, discussion about those laws follows. The discussion is tripartite, focusing on the consistency of ‘Umar II’ overall personality and character, the evolution of the identity of Muslim architecture, and the emergence of the first Muslim architectural deviations.